Compliance with Vulva Hygiene During Menstruation at Ibnu Mas'ud Puteri Islamic Boarding School, South Hulu Sungai Regency: A Descriptive Analysis: Kepatuhan Vulva Hygiene Selama Menstruasi di Pondok Pesantren Ibnu Mas’ud Puteri Kabupaten Hulu Sungai Selatan: Sebuah Analisis Deskriptif - Melinda Restu Pertiwi; Aulia Sofei; Diana Hardiyanti (Salando Health Journal, 2024)
Vulva hygiene care during menstruation should change pads regularly, which is 3-4 Background: Vulva hygiene care during menstruation is essential to prevent reproductive tract infections. However, poor hygiene behavior is still often found in adolescents, especially in Islamic boarding schools. This study aims to evaluate the level of vulva hygiene compliance during menstruation at the Ibnu Mas'ud Puteri Islamic Boarding School, South Hulu Sungai Regency. This descriptive study involved 170 students as a total sample. Data were collected using a validated questionnaire (Cronbach's Alpha = 0.85) and analyzed descriptively. Most respondents (91.6%) were moderately compliant, while 8.4% were less compliant. Influencing factors include knowledge, attitudes, and family support. The majority of students are quite obedient in maintaining vulva hygiene during menstruation, but additional education programs are still needed to increase compliance in groups that are less compliant.